2011
DOI: 10.21608/jssae.2011.55708
|View full text |Cite
|
Sign up to set email alerts
|

Improving Phosphorus Use Effeciency and Its Effect on the Productivity of Some Crops

Abstract: A field experiment was carried out in two successive seasons at El-Ismailia Agric. Res. Station, ARC, in El -Ismailia Governorate, Egypt, to study the efficiency use of two different sources of P fertilizer i.e. superphosphate (SP) versus rock phosphate (RP),both of them were used with three levels (0, 22 and 30 Kg P2O5 fed -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…Similarly, Papadopoulos [10] found that the AR of barley plants decreased significantly when phosphorus doses applications were increasing in mono-ammonium phosphate (MAP), diammonium phosphate (DAP) and triple superphosphate (TSP) forms. Under field conditions, in contrast to our results, El-Etr et al [13] found that AR of corn and sesame plants were increasing when the phosphorus application increased. Also, K-Humate (K-H 12 ) application according to control (K-H 0 ) while AR of Bayraktar 2000 variety increased significantly by 12% (21.69%) at P 17.5 applications, it was decreased significantly by 40% (9.75%) at P 35 application and 12% (15.72%) as K-Humate average ( Table 3).…”
Section: Parameterscontrasting
confidence: 99%
See 3 more Smart Citations
“…Similarly, Papadopoulos [10] found that the AR of barley plants decreased significantly when phosphorus doses applications were increasing in mono-ammonium phosphate (MAP), diammonium phosphate (DAP) and triple superphosphate (TSP) forms. Under field conditions, in contrast to our results, El-Etr et al [13] found that AR of corn and sesame plants were increasing when the phosphorus application increased. Also, K-Humate (K-H 12 ) application according to control (K-H 0 ) while AR of Bayraktar 2000 variety increased significantly by 12% (21.69%) at P 17.5 applications, it was decreased significantly by 40% (9.75%) at P 35 application and 12% (15.72%) as K-Humate average ( Table 3).…”
Section: Parameterscontrasting
confidence: 99%
“…In addition to, as phosphorus average when phosphorus doses were increasing (P 17.5 = 17.5 and P 35 = 35 kg P ha -1 ) according to control (P 0 , 3.19 ton ha -1 ), the grain yield 11% and 12% respectively were increased significantly and when K-Humate did not apply depending on control (P 0 , 3.17 ton ha -1 ), %10 and %18 respectively were increasing significantly too (Table 1). A similar result, on bread wheat by [17][18][19], on durum wheat by Peker [20], on barley by Valizadeh et al [21], on corn by Saeed et al [22] and on corn and sesame by El-Etr et al [13] were stated that the plant grain yield increased significantly by increasing phosphorus application to the soil. The effect of the K-Humate application on the grain yield has changed according to the amount of phosphorus application.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations